SISTEM PENGENDALIAN INTERNAL PIUTANG DALAM MENGELOLA PIUTANG MACET (STUDI KASUS PADA UPK KECAMATAN CIPUTAT TIMUR) - Moh Tahang; Rasmawati AR; Melati Puspita Hakim; Dea Widya Anggraeni (JURNAL LENTERA BISNIS, 2023)
PNPM Mandiri Rural is a program to accelerate poverty alleviation in an integrated and sustainable manner. The vision of PNPM Mandir in rural areas is to realize the welfare and independence of the rural poor. Based on the vision, mission and strategies developed, PNPM emphasizes the importance of empowerment as the chosen approach in rural areas. Through PNPM Mandiri Rural it is hoped that the community will be able to complete the stages of empowerment, namely achieving independence and sustainability. The Mandiri Rural National Community Empowerment Program (PNPM) in East Ciputat District, South Tangerang City began operating in January 2017. For the community, especially MSMEs, they really feel the benefits of these Mandiri PNPM programs, especially for programs from funds provided lent by PNPM Mandiri Pedesaan. The collectibility of receivables over the last three years was in the percentage of collectibility I for the current category at 63%, collectibility II for the special mention credit category at 12%, collectibility III for the substandard category at 4% while collectibility for the IV category was doubtful at 3% and finally collectability V the bad credit category is 19%, with an average non-performing loan of 25%. This percentage shows that receivables over the last three years have not been good with current credit collectibility of 63% with the NPL being in the high risk category. With a percentage figure of 25%. From the conclusion of the percentage figures above, the effectiveness of controlling receivables based on the results of the NPL collectibility ratio is not good, but the circulation of receivables still continues today because the SPP program is a government program that is social assistance with a positive vision and mission to improve living standards by providing business financing for mothers. RTM (Poor Households) to become more independent and productive in developing businesses and opening up jobs, even on a small scale. Key words: Internal Control System, Bad Debt Management, Receivables